2017
DOI: 10.1177/1558944717725373
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Psychosocial Services Post Hand and Upper Limb Injury and Trauma: A Pilot Study

Abstract: Therapists appear to be biomechanically oriented which may impact outcomes. An inverse correlation was found where the less experience participants had, the more likely they were to refer to psychosocial services. The results emphasized the lack of psychosocial assessments, interventions, and referral services being used by therapists. Further education to therapists, third parties, and other health professionals is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Furthermore, pain intensity, catastrophic thinking, and magnitude of disability can be largely explained by psychological factors (Teunis et al, 2015). Unfortunately, psychological factors are often overlooked both in research and in clinical practice within hand therapy (Chown et al, 2018;Hannah 2011;Takata et al, 2019). Participants in our study experiencing stress or anxiousness upon arriving at therapy conveyed how these factors were somewhat reduced by the mind-body interventions, providing impetus for continued investigation of how mind-body interventions can mitigate psychological symptoms.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, pain intensity, catastrophic thinking, and magnitude of disability can be largely explained by psychological factors (Teunis et al, 2015). Unfortunately, psychological factors are often overlooked both in research and in clinical practice within hand therapy (Chown et al, 2018;Hannah 2011;Takata et al, 2019). Participants in our study experiencing stress or anxiousness upon arriving at therapy conveyed how these factors were somewhat reduced by the mind-body interventions, providing impetus for continued investigation of how mind-body interventions can mitigate psychological symptoms.…”
Section: Discussionmentioning
confidence: 82%
“…Many previous investigators have called for mental health screening and psychosocial services to be part of standard care for this patient population [ 9 , 13 , 16 , 20 , 21 , 23 , 35 , 36 ], but recent research suggests that such screening or services are not common amongst any hand trauma services [ 37 ]. Our study brings new knowledge to this field providing strong support for new models of care which recognize the associated mental health challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Although effective interventions for psychological disorders are available they are not widely used for hand patients. Chown et al (2018) surveyed occupational therapists and hand therapist and identified a lack of psychosocial assessments, interventions and referral services following hand and upper limb injury and trauma. They concluded that psychosocial factors are not typically being addressed during the rehabilitation process.…”
Section: Discussionmentioning
confidence: 99%
“…The theory is that the brain will then reprocess the thoughts without the previously associated negative emotions. These treatments are not widely available to patients with hand disorders and psychological symptoms with management focusing on the physical hand problem (Chown et al., 2018).…”
Section: Introductionmentioning
confidence: 99%